Mandibular chondroblastic osteosarcoma in a bovine - Case report - Peixoto, Tiago da Cunha; Silva, Danielle Nascimento; Araújo, Byanca Ribeiro; de Farias, Soraya Santos; Pinto, Marcela Próspero Rodrigues; Requião, Luciano Guimarães Tanajura; Muramoto, Caterina; Madureira, Karina Médici (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Peixoto T.C., Silva D.N., Araújo B.R., de Farias S.S., Pinto M.P.R., Requião L.G.T., Muramoto C. & Madureira K.M. [Mandibular chondroblastic osteosarcoma in a bovine - Case report.] Osteossarcoma condroblástico mandibular em um bovino - Relato de caso. Revista Brasileira de Medicina Veterinária 38(Supl.1):60-64, 2016. Departamento de Anatomia, Patoloiga e Clí- nicas Veterinárias, Escola de Medicina Veterinária e Zootecnia, Universidade Federal da Bahia, Av. Adhemar de Barros, 500, Ondina, Salvador, BA 40170- 110, Brasil. E-mail: tcpeixoto@ufba.br The objective of this work is to describe the clinical pathological and radiological aspects of mandibular chondroblastic osteosarcoma in a five year old bull. During the autopsy, there was a lush neoplastic proliferation affecting the left mandibular branch measuring 24 x 19.5 x 13 cm, multilobular aspect, that invaded the oral cavity, showed irregular surface with many exophytic nodules of difference sizes. When cut, the tumor had compact surface, whitish aspect, bone consistency and central necrosis. Microscopically, there were atypical proliferation of mesenchymal cells, marked pleomorphism and high mitotic index in large areas of bone matrix and chondroid. The diagnosis was based on clinical, pathological radiographic findings and confirmed by histopathological examination. This is the first report of primary mandibular chondroblastic osteosarcoma in bovine.